(untitled) (South Asian Journal of Agriculture, 2022)
Staphylococcus aureus is an emerging pathogen from dairy animals that can form biofilms in the udder of dairy cows affected by mastitis. The use of antibiotics in dairy farms leads to a decrease in bacteria, finally making healthy food. The aim of this study was to determine the occurrence, antibiotic susceptibility, and biofilm forming ability of S. aureus isolated from cow milk. A total of fifteen raw milk samples were collected from Mohammadpur, Narayangonj, Savar, Bosila, Siddheshwari and Norshingdi dairy farms for isolation of S. aureus. All the samples were highly loaded with Staphylococcus and the total staphylococcal count ranged from 105 to 106 cfu ml-1. Biochemical tests (TSI, catalase, oxidase, motility, MR/VP etc.) were performed for the confirmation of the Staphylococcal isolates. The 100% resistance was observed against oxacillin, erythromycin, cotrimoxazole, amoxicillin, cefixime and vancomycin. In contrast to these results, the isolates showed 100% sensitivity to gentamicin and ciprofloxacin. The sensitivity against kanamycin and tetracycline was observed to be variable. The present study reveals the presence of multidrug resistant S. aureus in milk. Therefore, appropriate control measures like proper sanitation of the place where the milking cows live, maintenance of hygiene before and after milking, using proper mechanical methods for milking with strict maintenance of sanitation etc. are needed to be ensured. South Asian J. Agric., 8(1&2): 13-19